(untitled) (Journal of Student Affairs in Africa, 2021)
Issues of social inclusion and difference within the co-curriculum are crucial. This article draws on themes central to a critical feminist framework of social inclusion and citizenship in HE to argue that the way in which co-curricular opportunities are traditionally structured at universities may exclude those students who are marginalised. It also suggests how we may minimise institutional, cultural and economic discrimination, thus giving most students an opportunity to flourish.